2015
DOI: 10.1021/jp511105v
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Photochemical Processes of Excited Singlet and Triplet [3n]Cyclophanes (n = 2–6) Studied by Emission Measurements and Steady-State and Laser Flash Photolyses

Abstract: Photophysical and photochemical features of [3n]cyclophanes (3nCPs) (n = 2-6) in solution were investigated by emission and transient absorption measurements. The studied 3nCPs show excimer fluorescence without locally excited fluorescence whereas some of them emit excimer phosphorescence in rigid glass at 77 K. The probability of excimeric phosphorescence from transannular π-electron systems was shown to strictly depend on the symmetric molecular structures. A feature of intersystem crossing from an excimeric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Since the first observation of excimer fluorescence from pyrene, several studies have been performed to understand the nature of singlet and triplet excimers by various spectroscopic techniques, such as steady-state absorption and emission spectra and time-resolved transient absorption spectra. Previous studies have shown that excimers dissipate the excitation energy and usually increase nonradiative transition . Recently, the systems have been reported to show new roles, such as enhancing phosphorescence quantum yield and facilitating singlet fission , and electron transfer .…”
Section: Introductionmentioning
confidence: 99%
“…Since the first observation of excimer fluorescence from pyrene, several studies have been performed to understand the nature of singlet and triplet excimers by various spectroscopic techniques, such as steady-state absorption and emission spectra and time-resolved transient absorption spectra. Previous studies have shown that excimers dissipate the excitation energy and usually increase nonradiative transition . Recently, the systems have been reported to show new roles, such as enhancing phosphorescence quantum yield and facilitating singlet fission , and electron transfer .…”
Section: Introductionmentioning
confidence: 99%